Reducing IT costs and ensuring safe operation with application of the portfolio management - Mozsar Kovacsne, Livia Alice (Serbian Journal of Management, 2017)
Large companies need to give focus on their cost components related to their information technology. Business growths is supported by their IT and hundreds or thousands of applications worldwide. Top level management needs to focus more on their information strategy and the applications they need to manage. A structured and transparent application landscape supports not only the current business but it also enables faster business growth for the future as well. Structuring and organizing the applications related to the various risks supports secure business and information operations within a company. Capturing the applications gives the companies an overview of their information costs and provides the possibility of measurement and control of their IT costs elements. Application portfolio management and information security management are important elements of the corporate strategies.